2011
DOI: 10.2139/ssrn.1884786
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change of Personality Across the Life Course: The Impact of Age and Major Life Events on Mean-Level and Rank-Order Stability of the Big Five

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(201 citation statements)
references
References 68 publications
18
180
3
Order By: Relevance
“…For instance, the study cited above (Specht et al, 2011) suggested that life satisfaction may serve to approximate how closely one fits one's roles for life, and thus this role commitment piece may serve as the true driving mechanism of personality development (see also, Roberts, Wood, & Caspi, 2008). As an example, one could think of mechanisms by which committing to an identity could promote forgiveness outside of subjective well-being (e.g., identity commitment leads to a stronger sense of who one is, which leads to a decreased likelihood that one feels that any single transgression is an attack on the self).…”
Section: Lack Of Additional Feedback Loopsmentioning
confidence: 99%
“…For instance, the study cited above (Specht et al, 2011) suggested that life satisfaction may serve to approximate how closely one fits one's roles for life, and thus this role commitment piece may serve as the true driving mechanism of personality development (see also, Roberts, Wood, & Caspi, 2008). As an example, one could think of mechanisms by which committing to an identity could promote forgiveness outside of subjective well-being (e.g., identity commitment leads to a stronger sense of who one is, which leads to a decreased likelihood that one feels that any single transgression is an attack on the self).…”
Section: Lack Of Additional Feedback Loopsmentioning
confidence: 99%
“…7) This is in line with other reports of personality change throughout the life span of surgeons. 28) Our results indicate that students with higher extraversion scores already have the “quick hands” needed for microsurgery. We assume that surgeons acquire higher emotional stability, openness, conscientiousness, and lower agreeableness through their surgical residency and that higher extraversion is endowed by nature.…”
Section: Discussionmentioning
confidence: 62%
“…Contrary to the view long espoused by trait theorists that personality traits are "essentially fixed by age 30" (McCrae & Costa, 1994), data from several large-scale studies provide ample evidence that there is meaningful and significant change in mean levels of personality traits throughout adulthood, with the general trend that most people show decreases in neuroticism and increases in agreeableness and conscientiousness from early to middle and even later adulthood (e.g., Specht, Egloff, & Schmukle, 2011). These patterns of findings cannot be attributed primarily to the unfolding of intrinsic maturational processes, as there is substantial interindividual variability in the direction and rate of change as well as cohort differences (e.g., Bleidorn et al, 2013;Mroczek & Spiro, 2007).…”
Section: Recent Research On Personality Development In Adulthoodmentioning
confidence: 67%
“…However, DET would also predict that most people are likely to maintain their rank order position on personality traits relative to their peers or age group (Izard et al, 1993) because personality traits tend to become more entrenched over time (Izard & Ackerman, 1997) as emotions become increasingly linked to other emotions and cognition to form stable self-concepts, and people seek out and create environments that confirm their self-concepts. The research on personality trait development, indeed, also provides robust evidence for the increasing rank order stability or consistency in personality traits in adulthood, at least until older age (e.g., Specht et al, 2011).…”
Section: Recent Research On Personality Development In Adulthoodmentioning
confidence: 86%